Analisis sustainability peformance pada perusahaan di bursa efek indonesia sebelum dan selama Covid 19 - Ahmad, Fia; Soepriyanto, Gatot (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study aims to explore differences in performance between the period before Covid 19 and the period during Covid 19. This study uses financial reports and corporate sustainability reports in various industries listed on the IDX as research objects and uses the Wilcoxon test as a method that compares the period before Covid 19, namely 2018 - 2019 and the period during Covid 19 in 2020. The results showed that there was a significant decrease in economic performance of 16.37, a significant increase in performance. social and environmental are 10.39 and 72.47, respectively. This decline in economic performance occurred as a result of the implementation of social distancing, restrictions on travel and tourism, and the decline in people's purchasing power. On the other hand, these regulations lead to a decrease in electricity consumption in the Java Bali area and a decrease in air pollution, especially in Jakarta. Meanwhile, the increase in social performance occurred due to the widespread assistance from companies for the surrounding community, especially those dealing with Covid 19.